Risk factors for the metabolic syndrome components of hypertension, diabetes mellitus, and dyslipidemia after living donor liver transplantation. Issue 4 (April 2020) - Toshima, Takeo; Yoshizumi, Tomoharu; Inokuchi, Shoichi; Kosai-Fujimoto, Yukiko; Kurihara, Takeshi; Yoshiya, Shohei; Mano, Yohei; Takeishi, Kazuki; Itoh, Shinji; Harada, Noboru; Ikegami, Toru; Soejima, Yuji; et al.
Abstract: Background: Metabolic syndrome (MS) is the most common long-term complication after liver transplantation, and it has been increasing in incidence. The aim of this study was to clarify the risk factors for each MS component -hypertension, diabetes mellitus, and dyslipidemia-after living-donor liver transplantation (LDLT), including characteristics of living-donors. Methods: Data related to clinicopathological parameters including MS components in 461 consecutive patients who underwent LDLT were analyzed retrospectively. Results: Prevalence of all MS components (hypertension, diabetes mellitus, and dyslipidemia) increased from 9.3%, 16.5%, and 7.2% before LDLT to 44.9%, 45.3%, and 50.8% after LDLT, respectively. By multivariate logistic regression analysis, the three factors, cyclosporine use (OR 2.086, P  = 0.001), recipient age (OR 1.036, P  = 0.001), and BMI (OR 1.072, P  = 0.026) were independent predictors for post-LDLT hypertension. Next, the three factors, male recipient (OR 2.471, P  < 0.001), recipient age (OR 1.039, P  = 0.002), and donor BMI (OR 1.124, P  = 0.012) were independent for post-LDLT diabetes mellitus. The four factors, cyclosporine use (OR 2.015, P  = 0.001), prolonged prednisolone use (OR 1.928, P  = 0.002), recipient age (OR 1.019, P  = 0.037), and GRWR (OR 0.316, P  = 0.037) were independent for post-LDLT dyslipidemia as well. Conclusions: Not only recipient-related factors but also donor-related factors were independently associated with each targeted post-LDLT MS component.